Pengaruh Orientasi Pasar Terhadap Pembelajaran Karyawan Pada PT. XYZ - Junengsih Junengsih; Arif Nugroho; Dewi Arisansi; Sahril Mujani (Eqien - Jurnal Ekonomi dan Bisnis, 2023)
The purpose of this study was to determine the effect of market orientation on employee learning at PT. XYZ. This study used a simple random sampling technique, the sample used in this study amounted to 100 samples. The data collection method uses a system of primary data, namely observations, interviews and questionnaires, and secondary data, namely literature study. Instrument testing used validity and reliability tests, and for data analysis methods used quantitative data frequency distribution analysis, simple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, and t test analysis. the result is the effect of each independent variable on the dependent variable, namely: Market orientation has a tcount value of 4.027 with a significant 0.05, namely 0.00 the t-tube value shows greater than the t-table value of 4.027 1.984. The results of the partial test (t statistical test) on the market orientation variable have a t-count value of 4.027 with a significant 0.05, namely 0.00. It can be concluded that market orientation influences employee learning. This shows that the higher the market orientation, the higher the learning orientation.